Penguatan Karakter Mandiri Anak Usia Dini Melalui Kegiatan KKM PIAUD di Desa Situhiang - Diansyah, Diansyah; Rohmatin, Rohmatin; Amani, Halwa Ratu; Sonia, Evi Siti; Rosidah, Lilis Sari; Rosadi, Syahrazz Rifqah (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Early childhood is a critical period for developing independence (self-help, responsibility, confidence). In Situhiang Village (Cianjur), bullying and limited home stimulation were observed to hinder these outcomes. This community service aimed to strengthen children’s independent character through the Early Childhood Islamic Education (PIAUD) Student Community Service (KKM) using an Asset-Based Community Development (ABCD) approach. Activities were co-designed with parents, PAUD teachers, and community leaders (5D: Discover–Dream–Design–Define–Destiny). Data were collected through participatory observation, brief pre–post field notes, and weekly reflections with parents/teachers. The program fostered more active participation, improved willingness to speak up, and increased independence in daily routines (e.g., tidying up toys, washing hands, simple self-help tasks). These gains were supported by a safer learning climate and consistent reinforcement at home. The findings highlight ABCD’s practicality for character education in rural settings and underline the importance of family–school–community collaboration. Future work should incorporate clearer measurement tools and follow-up monitoring to assess sustainability.